Women and Indigenous Knowledge : A South-South Perspective - Pidatala, Krishna; Rahman Khan, Aisha (World Bank, Washington, DC, 2012)
The gendered nature of Indigenous Knowledge - IK - is often overlooked, marginalized or neglected. While the differences may tend to be more subtle in industrial countries, the same cannot be said of developing countries. Information, especially IK-related information, tends to be viewed, perceived, and acted upon differently by the different genders. This note seeks to provide an understanding of the role of gender, and the way it impacts the intrinsic value of local knowledge systems, critical to the understanding, interpretation, and dissemination of indigenous knowledge. As a result of this gender differentiation and specialization, the IK and skills held by women, often differ from those held by men, affecting patterns of access, use, and control, thus resulting in different perceptions and priorities for the innovation and use of IK. It also impacts the way in which IK is disseminated, documented, and passed on to future generations. In attempting to achieve cross-regional exchange of women's IK, the Bank organized the Indigenous Knowledge Program, a study tour to South Asia, and the key to some success stories, as observed in the region, resulted from having women involved in planning, and implementation in projects at the grassroots level. The note reviews aspects in traditional medicine, medicinal plants, food security, as well as the level of information communications technology, and early childhood development. In this context, some adaptations concerning women were found, namely, bottom-up approach; battling HIV/AIDS; and innovations in early childhood development.